2016
DOI: 10.1007/s12031-016-0741-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of Long Non-Coding RNAs in Serum of Patients with Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic progressive inflammatory disease of the central nervous system (CNS) that leads to severe neurological disability. There is an interest in potential biomarkers that could provide information predicting disease activity and progression. Long non-coding RNAs (lncRNAs) have been reported to be involved in the pathogenesis of various human disorders, such as oncologic, cardiovascular, and neurodegenerative diseases. No studies have so far explored a potential link between lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 33 publications
2
71
2
Order By: Relevance
“…Notably, LINGO1 interacts with APP 37 and is a promising target for multiple sclerosis (MS) with a LINGO1 neutralising antibody in Phase II trials 38 . Similarly, NEAT1 , a regulatory non-coding RNA that is found increased in serum of patients with relapsing-remitting MS 39 , was highly expressed in a1, a2 and o2 AD subclusters (Fig. 3c, k).…”
Section: Resultsmentioning
confidence: 85%
“…Notably, LINGO1 interacts with APP 37 and is a promising target for multiple sclerosis (MS) with a LINGO1 neutralising antibody in Phase II trials 38 . Similarly, NEAT1 , a regulatory non-coding RNA that is found increased in serum of patients with relapsing-remitting MS 39 , was highly expressed in a1, a2 and o2 AD subclusters (Fig. 3c, k).…”
Section: Resultsmentioning
confidence: 85%
“…VDR is a nuclear receptor that heterodimerizes with the retinoid X receptor, which after ligation with 1,25(OH) 2 D recognizes vitamin D response elements (VDREs) within regulatory regions of targeted genes . Importantly, several studies have revealed that VD can impact the expression of lncRNAs and that peripheral blood mononuclear cells (PBMCs) and serum of patients with MS exhibit altered levels of lncRNAs compared with controls . Studies aiming to understand the mechanisms underpinning lncRNA regulation of gene expression have greatly benefited from the discovery of HOX transcript antisense intergenic RNA (HOTAIR), a lncRNA molecule encoded within the HoxC gene cluster on chromosome 12 and transcribed in an antisense manner with respect to the canonical HoxC genes .…”
Section: Introductionmentioning
confidence: 99%
“…For data analysis, the CT values of pre‐ and post‐stimulation were exported to an Excel file and uploaded into web portal at https://www.qiagen.com/dataanalysiscenter. CT values were normalized using as reference genes Ribosomal protein, large, P0 ( RPLP0 , NM_001002), ZNFX1 antisense RNA 1 ( ZFAS1 , NR_003604) and Growth arrest‐specific 5 ( non‐protein coding ; GAS5 , NR_002578) as previously described (Santoro et al, ).…”
Section: Methodsmentioning
confidence: 99%